ALACIP Young: contributions to a Latin American Political Science with a gender perspective (Papeles, 2023)
This presentation is part of the Debate called ‘Public policy and gender’. What is the role of the State?’, is a discussion held by the Political Science chair B and the Secretariat of Research and Transfer of the Faculty of Law and Social Sciences of the National University of Litoral (FCJS-UNL), on Thursday, August 25, 2022. We provide a reflection on the necessity for thinking about and developing a political science with a gender perspective based on the participation of the Executive Committee of the Youth Group in the Latin American Association of Political Science's (ALACIP Joven in Spanish) at the Conference as it is one of the self-managed projects selected for the 2022 call.
Keywords: Political science; gender perspective; feminisms